2022
DOI: 10.1111/ajt.16865
|View full text |Cite
|
Sign up to set email alerts
|

Sex and organ-specific risk of major adverse renal or cardiac events in solid organ transplant recipients with COVID-19

Abstract: While older males are at the highest risk for poor coronavirus disease 2019 (COVID‐19) outcomes, it is not known if this applies to the immunosuppressed recipient of a solid organ transplant (SOT), nor how the type of allograft transplanted may impact outcomes. In a cohort study of adult (>18 years) patients testing positive for COVID‐19 (January 1, 2020‐June 21, 2021) from 56 sites across the United States identified using the National COVID Cohort Collaborative (N3C) Enclave, we used multivariable Cox propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…We have previously shown that in the pre‐vaccine era, the outcomes after COVID‐19 infection vary by SOT type, with heart and kidney recipients at the greatest risk for most complications. 8 A later study examined the differential antibody response to a second dose of the mRNA vaccine in SOT recipients by organ type, and demonstrated the lowest seroconversion rate in heart (18.8%), followed by kidney (45.5%), and liver (69.4%) recipients. However, the total SOT included in the study was only 226, and lung transplant recipients were not included, with no assessment of clinical outcomes following vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that in the pre‐vaccine era, the outcomes after COVID‐19 infection vary by SOT type, with heart and kidney recipients at the greatest risk for most complications. 8 A later study examined the differential antibody response to a second dose of the mRNA vaccine in SOT recipients by organ type, and demonstrated the lowest seroconversion rate in heart (18.8%), followed by kidney (45.5%), and liver (69.4%) recipients. However, the total SOT included in the study was only 226, and lung transplant recipients were not included, with no assessment of clinical outcomes following vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes after BTCo included MARCE defined as a composite of acute kidney injury (AKI) with or without dialysis, acute myocardial infarction, angina, stent occlusion/thrombosis, stroke, transient ischemic attack, congestive heart failure or death from any cause, 8 major adverse cardiac events (MACE) in isolation, renal failure requiring dialysis or AKI not requiring dialysis, death from any cause, hospitalization, and severe COVID‐19 (including need for ventilation, extra corporeal membrane oxygenation [ECMO], or death) in the 90 days following COVID‐19 diagnosis. In the SOT population, we also examined the outcomes of acute rejection and graft loss.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heart transplant (HTX) recipients constitute a high-risk population of patients in the setting of COVID-19. 7 - 9 In addition to harboring higher number of comorbidities, 10 HTX patients have a suppressed immune state, which has been a controversial risk factor for the development of more severe COVID-19 or poor clinical outcomes. 7 , 8 , 11 …”
Section: Introductionmentioning
confidence: 99%